Programa para el aprovechamiento de los residuos vegetales provenientes de la tala, poda y jardinería para la Corporación Monte & Ciudad. (2021)
The waste generated from logging, pruning and gardening activities, being chipped, always generates a great problem at a local and global level; There has been a problem with them, whether organic or inorganic generated by public or private companies and the community. Over time they debate on how this waste can be used for the different entities that generate it, clearly reducing and mitigating the misuse of it, which is why various plans were implemented worldwide so that said organic waste in this case are usable in different areas, from its initial stage to its final stage